An Assessment of Workload on Upper Limbs When Caregiver Change the Nursing Trousers (Journal of Fiber Bioengineering and Informatics, 2013)
In this research, movements of the upper limbs of caregivers when putting on/removing the dummy'snursing care clothes with different designs were measured using electromyography (EMG) and videofilming. Caregivers' sensory assessments of the burden caused by their services were also investigated todetermine how the physiological burden in the upper limbs and sensation of burden relate to each other.Subjects were 10 healthy women aged 23 ± 3 years, with a height of 159.7 ± 8.7 cm and weight of 50.5± 8 kg. None of the women had ever provided nursing care to anyone. For this experiment, four kinds ofsamples were used. By combining EMG and questionnaires, it was made possible to quantify the burdenon the upper limbs, which cannot be assessed solely according to work time. Differences in the workloadassociated with trousers having different designs were also studied. Also, the possibility was suggestedthat by taking such an approach, nursing care clothes may be developed that would further reduce theburden on caregivers while providing nursing care.